The Imputed Effect of the 2018 Tariffs on US Factor Shares - Thompson, Alexi; Thompson, Henry (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2024)
The discretionary 2018 increase in the average tariff from 2% to 12% will have broad effects across the US economy reflected in the present predicted factor shares of capital, labor, skilled labor, and energy input. Error correction estimates of a Linear Almost Ideal Demand System introduce the price of import competing goods as a proxy for the average tariff in annual 1983-2018 data. The historically large tariff increase will boost the rising capital share of income while the declining labor share accelerates and the rising skilled labor share reverses. Capital is the only winner due to the increased tariffs.